Colloidal few layered graphene–tannic acid preserves the biocompatibility of periodontal ligament cells - Ben Ammar, Teissir; Kharouf, Naji; Vautier, Dominique; Ba, Housseinou; Sudheer, Nivedita; Lavalle, Philippe; Ball, Vincent (Beilstein Journal of Nanotechnology, 2025)
Dental diseases pose a global health concern. In addition to medication and care, the use of biocompatible and even bioactive dental materials can contribute to global oral health. Among such materials, nanomaterials begin to be used. In this context, the incorporation of graphene-based materials into dental biomaterials could offer advantages such as increased mechanical strength. Nevertheless, biocompatibility issues still hinder their adoption. In this study, a biocomposite of few-layered graphene and tannic acid (FLG–TA) was synthesized through a straightforward, bio-based methodology. Physicochemical characterizations elucidated the structural and morphological attributes of the biocomposite. By incorporating antioxidant TA molecules onto the FLG surface, the biocomposite dynamically mitigated reactive oxygen species, demonstrating no cytotoxicity to periodontal ligament cells up to 200 µg·mL−1 while promoting cellular adhesion and maintaining chromatin integrity. Overall, because of its favorable biocompatibility FLG–TA holds promise as a novel biomaterial for dental applications.
Keywords: antioxidant properties; biocompatibility; dental applications; few layered graphene–tannic acid biocomposite (FLG–TA); periodontal ligament cells (PDL)